2017
DOI: 10.20471/acc.2017.56.03.11
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Pain Management after Carpal Tunnel Syndrome Surgical Treatment: Comparing Practice with Guidelines

Abstract: The management of postoperative pain after carpal tunnel syndrome surgical treatment at a tertiary hospital was analyzed and compared with the guidelines for perioperative pain management. This retrospective study included 579 patients operated on for carpal tunnel syndrome at the Split University Hospital Center in Split, Croatia. The following key data were collected from patient medical records: age, gender, type and dosage of premedication, type and dosage of anesthesia, type and dosage of postoperative an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
1
3
0
Order By: Relevance
“…Pain catastrophizing and pain anxiety are relatively common phenomena [23,[29][30][31][32]. Some studies suggest that effective treatment of perioperative pain is important for the quality of life and patient satisfaction after CTR [28]. In the present study higher levels of all assessed negative emotions in patients declaring "postoperative pain" were noted.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Pain catastrophizing and pain anxiety are relatively common phenomena [23,[29][30][31][32]. Some studies suggest that effective treatment of perioperative pain is important for the quality of life and patient satisfaction after CTR [28]. In the present study higher levels of all assessed negative emotions in patients declaring "postoperative pain" were noted.…”
Section: Discussionsupporting
confidence: 54%
“…It may be associated with proper treatment of perioperative pain in the past and good experiences with past surgeries [26]. Nevertheless, attention should be paid to the treatment of perioperative pain in CTR, since some studies revealed VAS pain scores of above 5 in the first several hours after CTR [27,28]. In the present study mean VAS score for preoperative pain was 6.8.…”
Section: Discussionmentioning
confidence: 50%
“…4 Even with the use of a minimally invasive technique, such as endoscopic, many patients report similar persistent pain, frequently leading them to the indiscriminate use of strong analgesic. 5,6 These persistent pains may be caused by sectioning the TCL in a zone with numerous nerve endings.…”
Section: Introductionmentioning
confidence: 99%
“…Postoperative pain is a type of acute pain caused by surgical trauma and the associated inflammatory response 1 . Almost all patients undergoing a surgical procedure experience some degree of pain, but not all pain is adequately treated 2,3 . In the authors' experience, one of the first questions that patients ask after the surgical procedure is "will it hurt?…”
Section: Introductionmentioning
confidence: 99%